2010
DOI: 10.2466/07.17.pms.111.6.694-700
|View full text |Cite
|
Sign up to set email alerts
|

Appearance (Ethnic Origin) of Requester Affects the Foot-In-The-Door Technique

Abstract: A study was designed to examine the effect of the appearance of the requester within one of the variants of the foot-in-the-door paradigm, that is, the foot-in-the-door with implicit demand described by Uranowitz in 1975. A confederate (Black vs. Blanc vs. Beur2) approached the participant in a park and presented a small request. Three steps further, the confederate "accidentally" dropped 30 sheets of paper. Whether or not the participant helped the confederate in retrieving the dropped pamphlets was recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The level of action identification is important to enable people to be committed, but the source of the request seems important as well: in a field experiment, Fointiat and Saint-Bauzel (2010) found that the FITD was ineffective if the requester was not of the same ethnic appearance as the participants. Congruent with the results of Eastwick and Gardner (2009) obtained in virtual environments, this outcome shows that even under the influence of established compliance procedures, individuals are not automatically committed to anybody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of action identification is important to enable people to be committed, but the source of the request seems important as well: in a field experiment, Fointiat and Saint-Bauzel (2010) found that the FITD was ineffective if the requester was not of the same ethnic appearance as the participants. Congruent with the results of Eastwick and Gardner (2009) obtained in virtual environments, this outcome shows that even under the influence of established compliance procedures, individuals are not automatically committed to anybody.…”
Section: Discussionmentioning
confidence: 99%
“…The level of action identification is important to enable people to be committed, but the source of the request seems important as well: in a field experiment, Fointiat and Saint-Bauzel (2010) found that the FITD was ineffective if the requester was not of the same This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Implications For Researchersmentioning
confidence: 99%
“…For the last five decades, this social influence strategy has been well-documented and empirically validated (Dillard et al, 1984;Burger, 1999;Pascual and Guéguen, 2005). It still spikes interest among researchers (Dolinski, 2009(Dolinski, , 2012Fointiat and Saint-Bauzel, 2010;Saint-Bauzel and Fointiat, 2012;Pascual et al, 2013;Gamian-Wilk et al, 2018). The two metaanalyses conducted on FITD show a moderate effect (Beaman et al, 1983;Dillard et al, 1984).…”
Section: Introductionmentioning
confidence: 99%